Finding a new prince for management science: The antithesis to the Machiavellian Prince - Khan, Khurram Ellahi; Bhatti, Omar Khalid (Turkish Entrepreneurship and Business Ethics Association, 2019)
Machiavelli's The Prince has been cherished for more than 500 years, withits various facets used by scholars and researchers of management sciences. But with the dawn of positive organizational scholarship, the Machiavellian prince with his dark aspects does not appear compatible. Hence, the emerging field, resting more on humans' positive side, is also in need of an idol the way Machiavelli's The Prince has been idolized through the traditional views of management and business. As a result, the current study has reviewed Prince Myshkin, the protagonist in Dostoevsky's The Idiot as the alternative and antagonist to Machiavelli's style. Hence the current study identifies the possible ethical implications in human resource management which can be guided through the character of Prince Myshkin. The study also analyzes how two different princes (i.e.,Prince Myshkin and Machiavelli's prince) guide managers under similar situations, thus guiding managers to deal in contemporary tones with the way of the new prince (i.e., Prince Myshkin).
Keywords: Fiction For Business Ethics; Machiavelli; Machiavellian Prince; Prince Myshkin; Ethical Managers